A Guide to Japanese architecture, with an appendix on important traditional buildings (Tokyo, 1971)
This guidebook is a collection of the most outstanding of the postwar buildings with a sample selection of some of the most famous traditional Japanese architectural classics.
Keywords: Architecture; Japan